Src regulates insulin secretion and glucose metabolism by influencing subcellular localization of glucokinase in pancreatic β‐cells. Issue 2 (13th September 2015) - Sato, Hiroki; Nagashima, Kazuaki; Ogura, Masahito; Sato, Yuichi; Tahara, Yumiko; Ogura, Kasane; Yamano, Gen; Sugizaki, Kazu; Fujita, Naotaka; Tatsuoka, Hisato; Usui, Ryota; Mukai, Eri; et al.
Abstract: Aims/Introduction: Src, a non‐receptor tyrosine kinase, regulates a wide range of cellular functions, and hyperactivity of Src is involved in impaired glucose metabolism in pancreatic β‐cells. However, the physiological role of Src in glucose metabolism in normal, unstressed β‐cells remains unclear. In the present study, we investigated the role of Src in insulin secretion and glucose metabolism. Materials and Methods: Src was downregulated using small interfering ribonucleic acid in INS‐1 cells, and glucose‐induced insulin secretion, adenosine triphosphate content, intracellular calcium concentration, glucose utilization and glucokinase activity were measured. Expression levels of messenger ribonucleic acid and protein of glucokinase were examined by semiquantitative real‐time polymerase chain reaction and immunoblotting, respectively. Cells were fractionated by digitonin treatment, and subcellular localization of glucokinase was examined by immunoblotting. Interaction between glucokinase and neuronal nitric oxide synthase was estimated by immunoprecipitation. Results: In Src downregulated INS‐1 cells, glucose‐induced insulin secretion was impaired, whereas insulin secretion induced by high K + was not affected. Intracellular adenosine triphosphate content and elevation of intracellular calcium concentration by glucose stimulation were suppressed by Src downregulation. Src downregulation reduced glucose utilization in the presence of high glucose, which was accompanied by a reduction in glucokinase activity without affecting its expression. However, Src downregulation reduced glucokinase in soluble, cytoplasmic fraction, and increased it in pellet containing intaracellular organelles. In addition, interaction between glucokinase and neuronal nitric oxide synthase was facilitated by Src downregulation. Conclusions: Src plays an important role in glucose‐induced insulin secretion in pancreatic β‐cells through maintaining subcellular localization and activity of glucokinase. Abstract : In INS‐1 rat insulinoma cells, down‐regulation of Src by small interfering RNA reduced glucose‐induced insulin secretion due to impaired glucokinase activity by translocation of the enzyme from cytosol to membrane fraction. Our study indicates that Src plays an important role in maintaining glucokinase activity and glucose‐induced insulin secretion in pancreatic β‐cells.